Keeping the European Faith. Collective Identity Before and After the Euro-Crisis - Ettore Recchi (Coordinamento SIBA, 2014)
Media discourses have conveyed the message that European identity has been severely undermined by the Euro-crisis. We test this contention with Eurobarometer data. Conceptually we distinguish two dimensions of collective identity: ‘image’ and ’belonging’. We surmise that economic downturns can alter the superficial layer of identity (image-like assessments), but not its underlying substance (belonging-like assessments) which depends on deeply ingrained socio-psychological mechanisms. These two dimensions are expected to be affected by the crisis in different ways: the image being a more volatile reflection of historical circumstances, and the sense of belonging being more stable over time.